Tuber Cinereum Diverticula in a 28-Month-Old with Xq21 Deletion Syndrome - Matthew T. Whitehead; Gilbert Vezina (Case Reports in Radiology)
A developmentally delayed 28-month-old male toddler was referred to us for brain MRI. Imaging revealed corpus callosum dysgenesis, forniceal hypoplasia, vermian hypoplasia, and hypothalamic dysmorphism characterized by tuber cinereum diverticula. Subsequent chromosomal microarray showed an Xq21 deletion. We present a case of Xq21 deletion syndrome with midline brain anomalies and a novel hypothalamic malformation.